Reconceptualizing social work in times of crisis: An examination of the cases of Greece, Spain and Portugal. (July 2014) - Ioakimidis, Vasilios; Santos, Clara Cruz; Herrero, Ines Martinez
What started as a peripheral banking crisis in 2008 within five years triggered the deepest recession Europe has seen in decades, escalating to manifold socio-political crises. Under these circumstances, many social workers find themselves in a situation of extreme pressure and insecurity. Traditional theories and orthodox practices are now challenged by frontline social workers. This article explores such a 'reconceptualization' process, evaluating recent developments and changes in Spanish, Portuguese and Greek social work. We argue that the current crisis has generated a profound (re)politicization of social workers which leads to the redefinition of the core values and principles of social work.